THE USE OF BIG BOOK MATHEMATICS MEDIA ON STUDENT LEARNING OUTCOMES ON BUILDING MATERIAL FLAT CLASS IV MIN 11 ACEH MIDDLE - Putri Rahmi; Ifna Fawati; Saifullah Idris; Zikra Hayati (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
The main problem in this research is that the process of learning mathematics in plane material only relies on memorizing formulas, this occurs in students who do not understand the material. This research aims to determine the influence of the big book mathematics media on the learning outcomes of class IV MIN 11 Central Aceh students. The research was conducted using quantitative methods with a Nonequivalent Group Design. The population in this study were all class IV students at MIN 11 Central Aceh, while the sample was class totaling 16 students and class totaling 14 students. This research instrument uses a learning outcomes test sheet and the data collection technique used is the test technique and uses the t-test in analyzing the data. Based on the results of the analysis that has been carried out, the average score obtained in the Pre-Test for the experimental class was 50.642 and for the control class with an average score of 46.437. Meanwhile, in the Post-Test, the average score obtained by the experimental class was 74.5 and the control class had an average score of 62.81. The results of statistical analysis obtained = 2.1047 and = 1.70, because > then Ho is rejected and Ha is accepted. Kerwords: Big Book Math Media, Learning Outcomes, Two-Dimentional Figure